Literasi, Sikap, Inklusi, Perencanaan Keuangan terhadap Perilaku Manajemen Keuangan UMKM Batik di Kabupaten Purrbalingga - Putri, Galih Mutiara; Koesoemasari, Dian S.P.; Rokhayati, Isnaeni (Goodwood Akuntansi dan Auditing Reviu, 2024)
Purpose: This study aims to determine and analyze the effect of financial literacy, financial attitudes, financial inclusion, and financial planning on financial management behavior on UMKM Batik players in Purbalingga Regency. Research methodology: This research uses quantitative methods by distributing questionnaires to respondents. The data analysis in this study was carried out with the help of IBM SPSS software version 26. The population in this study was 95 using random sampling technique with a sample size of 75 respondents who were UMKM Batik business actors in Purbalingga Regency. Results: The results showed that financial literacy, financial attitudes, financial inclusion and financial planning have a positive and significant influence on financial management behavior on UMKM Batik actors in Purbalingga Regency. Limitations: The R-Square value is quite low at 49.9%. Based on this, there are about 50.1% other factors that influence financial management behavior in this study, such as financial knowledge, income, education level, and personality. Contribution: This research can be used as an academic literacy reference related to financial management behavior in UMKM in terms of financial literacy, financial attitudes, financial inclusion, and financial planning. The results of the study can also be used as a benchmark for UMKM Batik actors in implementing financial literacy, financial attitudes, financial inclusion, and financial planning in UMKM.